Synthesis and Characterisation of Novel Mercuric Complexes - Turwatkar, S.L.; Mehta, B.H. (Asian Journal of Chemistry, 2010)
The current interest in the coordination chemistry of azomethine group of various organic molecules arises from their wide ranging applications. The complexes were obtained from the interaction of mercuric(II) chloride with the different substituted Schiff bases. These complexes were characterised by using electrode absorption spectra and IR data. The results indicate that the metal ions coordinate with the azomethine nitrogen atom of the Schiff base. Assignments of the bands of the electronic absorption spectra are made and various ligand field parameters were calculated. Based on this diagnosis the complexes were assigned tetrahedral structure.